Performance and carcass traits of Landrace swine, from Pedigree vs. comercial strata - Larrambebere, Walter H. Saralegui; Costa, Cláudio Nápolis (Pesquisa Agropecuaria Brasileira, 2014)
One experiment was conducted in Concórdia, SC (1983), comparing the performance of Landrace pigs from pedigree (A) and commercial (B) strata, utilizing 16 castrated males and 16 females, by stratum. The experimental design was entirely at random, with four treatments, in a factorial scheme (2 x 2), with the factors stratum and sex, and four replications by treatment. The pigs were tested from 30 to 100 kg liveweight in group test under ad libitum feeding conditions. Superiority in the performance of the stratum (A) pigs, for "eye muscle" area, lean/fat ratio and carcass length. The (B) stratum was superior for the average daily gain 130- 100 kg). Feed conversion, average daily gain from birth, back-fat thickness, dressing and ham percentages, were similar from analysis of variance.
Keywords: pedigree stratum